2021
DOI: 10.1111/acfi.12838
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID‐19 on the global stock market

Abstract: This paper investigates the effect of COVID‐19 on the global stock market. Specifically, we test whether the growth in the number of confirmed cases/deaths affects market quality, measured by return, realised volatility, jumps and co‐jumps for 43 stock indices around the world. We find that an increase in the growth rate of the number of confirmed cases increases volatility and jumps while reducing return. Further, we explore whether economic, financial and political risks play any significant role in the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 67 publications
5
31
0
Order By: Relevance
“…They investigate the effects of COVID cases and containment measures, as well as country spillovers on 45 stock markets, and find evidence of negative spillover effects from containment measures. Chatjuthamard et al ( 2021 ) employ a panel with 43 different stock indices and verify that the growth rate of COVID cases significantly reduces the stock market performance. Heyden and Heyden ( 2020 ) use a panel of U.S. and European stocks to conduct an event analysis on the effects of the arrival of COVID in a country and the first policy responses on those stocks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They investigate the effects of COVID cases and containment measures, as well as country spillovers on 45 stock markets, and find evidence of negative spillover effects from containment measures. Chatjuthamard et al ( 2021 ) employ a panel with 43 different stock indices and verify that the growth rate of COVID cases significantly reduces the stock market performance. Heyden and Heyden ( 2020 ) use a panel of U.S. and European stocks to conduct an event analysis on the effects of the arrival of COVID in a country and the first policy responses on those stocks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our results provide evidence of volatility spillovers across nations, as the escalation in volatility as a result of the pandemic in one country, leads to an increase in uncertainty across the global economy ( Shahzad, et al, 2021 ). This is because Chatjuthamard, et al (2021) provide evidence that a rise in the number of confirmed COVID-19 cases enhances market volatility and jumps. Also, Zaremba et al (2021) report that COVID-19-related restrictions including lockdowns may adversely affect the trading volume in financial markets.…”
Section: Resultsmentioning
confidence: 97%
“…In this vein, Fernandes (2020) examined how COVID-19 impacts the industries and the economic potential across 30 countries providing insights into how long it would take for the effects of the pandemic shock to dissipate in terms of GDP and sectoral effects. Comparing traded markets, in a study by Chatjuthamard et al (2021) it was shown that an increase in the growth rate of the number of confirmed cases increases market volatility and jumps while reducing return. The intuition here is that while traders generally welcome market volatility as it may present opportunities ( Haar and Gregoriou, 2021 ), systematically profiting from purely non-predictable chaotic events, is not possible.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding the policy responses to the COVID-19 pandemic, Guven et al (2022) argued that state aid programmes in selected emerging econo-mies have positively influenced the stock market and effectively reduced the negative impact of the daily growth of confirmed infections and deaths. Moreover, analysing the effects of the pandemic on financial markets, Chatjuthamard et al (2021) argued that an increase in infections negatively influences stock market returns, whereas the impact is more substantial in the countries with a higher financial risk. Wang et al (2021) found a negative correlation between government responses and infection rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, whether there is a close link between the number of confirmed cases, deaths and economic indicators during the COVID-19 pandemic remains uncertain. Studies have analysed the impact of confirmed COVID-19 cases and deaths on the stock market (Chatjuthamard et al, 2021;Guven et al, 2022), economic growth (Feng et al, 2022), industrial production in selected OECD countries (Apergis & Apergis, 2021) and unemployment in the United States (Matthay et al, 2021) and five European Union (EU) countries (Su et al, 2021). However, no comprehensive investigation has analysed the interconnections between the COVID-19 pandemic and macro-economic indicators in the EU.…”
Section: Introductionmentioning
confidence: 99%